Transmission of SARS-CoV-2 between humans and company animals (Research, Society and Development, 2022)
Faced with the current pandemic of the new coronavirus (COVID-19), many doubts have arisen in society and fake news has been disseminated on social media about the transmission of SARS-CoV-2 between animals and humans, thus increasing the number of animals abandoned by tutors after the beginning of the pandemic. This review brings information from studies carried out on COVID-19 and pets. A bibliographic review of scientific publications was carried out: periodicals, magazines, books and articles on the subject. With the results, it was observed that although dogs and cats are affected by the new coronavirus, their transmission to humans has not been confirmed, however, there are suspected cases that humans can transmit the virus to animals and that probably, only the cats can transmit the virus interspecies.